Enhancing Students' Mathematical Problem-Solving Skills through the Implementation of the Project-Based Learning (PjBL) Approach - Alifah Shofia Fuadah; Achmad Firmansyah (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2026)
This study aims to improve students' mathematical problem-solving skills through a Project-Based Learning (PjBL) approach. The type of research used is classroom action research, conducted at MAN Kota Blitar. The subjects of this study were 32 students of class X MIPA 1, while the object of the study was the implementation of the Project-Based Learning approach in relation to students' mathematical problem-solving abilities. The instrument used in this research was a test. The results of the study indicate that the implementation of the Project-Based Learning (PjBL) approach in class X MIPA 1 at MAN Kota Blitar successfully enhanced students' problem-solving skills in trigonometry. This was evident from the improvement in students' learning evaluation results, particularly in their mathematical problem-solving abilities. In the first cycle, 14 students (44%) demonstrated good problem-solving skills, while in the second cycle, the number increased to 26 students (81%). Thus, there was a 37% increase in the percentage of students with good mathematical problem-solving skills between the first and second cycles.